Matematyka
Adaaa2020
2017-06-24 03:24:19
Zapisz w postaci sumy algebraicznej A) (x-1)(x²+ x+1) B) (x²-x+1)(1+x) C) (x²-6x+36)(x+6) D) (x-8)(x²+8x+64) E) (2x²-1)(4x²+2x²+1) F) (2x-1)³ G) (1-3x)³
Odpowiedź
SunRise21
2017-06-24 05:42:49

a) x3 + x2 +x -x2 -x-1 = x3 - 1 b) x2+ x3 -x -x2 +1 +x = x3 +1 c) x3 +6x -6x2 -36x +36x +216 = x3+6x -6x2 + 216 d)x3+8x2+64x-8x2-64x-512=x3-512 e)8x4+4x4 +2x2-4x2-2x2-1=12x4-4x2-1 f) (4x2-2x-2x1)(2x-1)=8x3-4x2-4x2+2x-4x2-2x+2x-1=8x3-12x2+2x-1 g) (1-3x-3x+9x2)(1-3x)= 1-3x-3x+9x2-3x+9x2+9x2-27x3=1-9x+27x2-27x3 Powinno być dobrze .

mennem
2017-06-24 05:44:04

[latex]a) (x-1)(x^{2}+x+1) = x^{3}+x^{2}+x - x^{2}-x-1 = x^{3}-1\\b) (1+x)(x^{2}-x+1 = x^{2}-x+1+x^{3}-x^{2}+x = x^{3}+1\\c) (x+6)(x^{2}-6x+36) = x^{3}-6x^{2}+36x + 6x^{2}-36x+216=x^{3}+216[/latex] [latex]d) (x-8)(x^{2}+8x+64) = x^{3}+8x^{2}+64x - 8x^{2}-64x -512=x^{3}-512[/latex] [latex]e) (2x^{2}-1)(4x^{2}+2x+1) = 8x^4}+4x^{3}+2x^{2}-4x^{2}-2x-1 =8x^{4}+4x^{3}-2x^{2}-2x-1 [/latex] [latex]f) (2x-1)^{3}=(2x)^{3}-3cdot(2x)^{2}cdot1 + 3cdot2xcdot1^{2}-1^{3} = 8x^{3}-12x^{2}+6x-1[/latex] [latex]g) (1-3x)^{3} = 1^{3}-3cdot1^{2}cdot3x+3cdot1cdot(3x)^{2}-(3x)^{3} =1-9x+27x^{2}-27x^{3}[/latex]

Dodaj swoją odpowiedź